Follicular dendritic cell sarcoma: a great mimicker with unpredictable clinical course—experience from a tertiary care cancer center in India - Ibrahim, Ajas; Mir, Mohmad Hussain; Bagdadi, Farhana Siraj; Sofi, Mushtaq Ahmad; Khanday, Abrar Rasool; Wani, Suhail Ahmad; Regmi, Sunil K.; Bhat, Mudasir Hamid; Syed, Nisar Ahmad; Guru, Faisal R.; Wani, Ulfat Ara; Qadri, Sumyra Khurshid (Frontiers in Oncology, 2025)
BackgroundFollicular dendritic cell sarcoma (FDCS) is a rare mesenchymal malignant tumor derived from follicular dendritic cells. FDCS arises mainly from lymph nodes and rarely are extranodal. Diagnostic dilemma occurs due to the same micromorphology as other sarcomas and lymphomas. Curative radical resection is the standard therapy, and adjuvant treatment is not defined. For unresectable disease, chemotherapy and radiotherapy are indicated with variable response rates. Due to its rarity, a standard treatment is not yet defined.ObjectiveThis study aims to analyze the clinicopathological features, treatment patterns, and survival outcome of FDCS cases in our institution.MethodologyThe study was conducted in the Department of Medical Oncology State Cancer Institute, Sher I Kashmir Institute of Medical Sciences (SKIMS), Srinagar, Jammu and Kashmir, India. Biopsy-proven FDCS patients were identified through the hospital-based registry from January 1, 2020 to December 31, 2023.ResultsA total of six patients were diagnosed during the study period. The median age was 28 years (range, 21–51 years). There were four male and two female patients, with male-to-female ratio of 2:1. Common symptoms were abdominal pain (50%) and cough and dyspnea (33.3%). Four patients (66.6%) had nodal involvement with retroperitoneum and mediastinum in two cases each. Three patients had extranodal involvement, with the colon in two and with the liver in one. Five patients were initially misdiagnosed as non-Hodgkin’s lymphoma, soft tissue sarcoma, neurogenic tumor, and carcinoma. The treatments offered were surgery, chemotherapy, targeted therapy, radiotherapy, and observation. Four patients were alive at a median follow-up of 12 months, with three patients having no evidence of disease and one case living with the disease. Two patients had succumbed to the disease.ConclusionThe study described the clinicopathological characteristics, diagnostic challenges, and management difficulties in FDCS patients. Due to the rarity of this disease, high expertise is needed to diagnose FDCS; otherwise, the diagnosis usually gets delayed.